Penyuluhan tentang Kekerasan Psikis Anak melalui Program “Rumah Aman Mendukung Perkembangan Anak” di Desa Nusawungu - Anisah Fitri; Kurnia Anoem Milandea; Raissa Aldora; Amelia Kartika; Mardiansyah Mardiansyah; Meitha Yesi Rahmawati; Afrina Syafriyanti; Ika Yulida Hakim; Ulil Albab (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Psychological violence against children remains a critical issue that is often overlooked because it does not leave visible physical injuries, yet its long-term consequences can significantly hinder children’s emotional, social, and academic development. Addressing this problem requires not only legal and institutional measures but also preventive efforts at the family and community levels. The Community Service Program (KKN) entitled “Safe Home Supporting Child Development” in Desa Nusawungu was designed as a community-based educational initiative to raise parents’ awareness of the importance of creating an emotionally safe home environment. The program was implemented through the Focus Group Discussion (FGD) method, which integrated structured material presentations, individual reflections using digital forms, and interactive group discussions. This combination allowed participants to gain knowledge, critically reflect on their own parenting practices, and share experiences with peers. The results revealed a notable increase in parents’ awareness of the detrimental effects of psychological violence on children’s well-being, their readiness to adopt positive parenting strategies, and their ability to identify challenges commonly faced in daily child-rearing practices. Moreover, participants expressed enthusiasm for sustaining similar activities in the future, highlighting the importance of continuous learning and the establishment of a parent learning community. The program demonstrated that simple, low-cost, and locally adapted interventions can effectively enhance parenting literacy, reduce the risk of psychological violence, and strengthen the developmental foundation of children during their golden age. These findings suggest that empowering parents through participatory education can serve as a replicable model for other communities facing similar challenges, thus contributing to the broader goal of ensuring children’s rights to grow in a safe and nurturing environment.